Tracing a Journey of Curriculum Redesign in Education: Are We There Yet? - Britt, Judy; Ferguson, Christine; Vare, Jonatha (Educational (Re)naissance, 2013)
The phrase “Are we there yet?” is used by travelers, often children who pose the question to gauge the distance and time remaining in a trip. How far have we traveled? How much longer will it be until we arrive at our destination? This article describes curriculum redesign for our early childhood and elementary education programs at Winthrop University in South Carolina. The details of this journey offer a roadmap of the program revision process that we encountered in our efforts to work toward continuous improvement in teacher education. By working with program faculty from within our college as well as faculty from the College of Arts and Sciences we accomplished our goals for curriculum redesign. As we enter the final phase of this 2-year endeavor, our writing documents the process that we encountered to achieve this goal.